Congenital disorders of autophagy: an emerging novel class of inborn errors of neuro-metabolism - Ebrahimi-Fakhari, Darius; Saffari, Afshin; Wahlster, Lara; Lu, Jenny; Byrne, Susan; Hoffmann, Georg F.; Jungbluth, Heinz; Sahin, Mustafa (Brain, 2016)
Mutations in autophagy genes cause childhood-onset multisystem diseases with predominant nervous system involvement and provide a ‘genetic window’ into autophag